Problems of using new pedagogical technologies in achieving successful experiences in modern cases (Pedagogy of Higher and Secondary Education, 2013)
Kovalʹchuk O. L. Problems of using new pedagogical technologies in achieving successful experiences in modern cases.This article is deals with a problems of use modern technologies for preparation of future competent specialists of speciality «Organization of air transportations» of air industry.
Keywords: technology; educational technology; advanced learning technologiey